Nanocrystalline cellulose-geniposide complex enhances gut-brain axis modulation for depression treatment - Tianyu Zou; Xiang Tang; Haiping Wang; Xiaolong Shang; Xiaoyu Liang; Xuemiao Ma (Communications Biology)
Abstract Depression, a major global health issue, is closely associated with imbalances in gut microbiota and altered intestinal functions. This study investigates the antidepressant potential of a composite of Geniposide (GP) and Nanocrystalline Cellulose (NCC), focusing on its effects on the gut-brain axis. Utilizing network pharmacology, GP was identified as a key compound targeting the BCL2 gene in depression management. Experimental approaches, including a chronic unpredictable mild stress (CUMS) model in mice, cellular assays, and fecal microbiota transplantation (FMT), were used to evaluate the composite’s effectiveness. Results indicate that GP activates the adenosine monophosphate-activated protein kinase (AMPK) pathway by upregulating BCL2, enhancing intestinal barrier integrity, and balancing gut flora. These mechanisms contribute to its positive effects on hippocampal function and depressive-like behaviors in mice, suggesting that the GP-NCC composite could be a promising avenue for developing depression therapies that target gut health.